TINGKAT ADOPSI PENGGUNAAN E - COMMERCE OLEH UMKM PADA MASA PANDEMI DI KOTA DEPOK - Restu Jati Saputro; Maswir Mawi; Hafniza Amir (Administratif Profesional, 2022)
MSMEs are one of the sectors affected by COVID-19, even though MSMEs are an alternative solution for social problems such as poverty and unemployment. The existence of a pandemic has led to the emergence of government policies, Large-scale social restrictions mobilization, which will have an impact on slowing economic activity and directly affect people's behavior in daily needs. This study discusses the adoption of the use of E-Commerce in the MSME sector in Depok City uses the TAM (Technology Acceptance Model) method by examining response of MSME activists in terms of usefulness, perceived ease, actual use and technology. The results show that the adoption of E-Commerce in Depok City has a moderate level of adoption, has a high usefulness value and a moderate level of convenience. Meanwhile, the technology capability used has a low value